Effect of dexamethasone on the expression of atrogin‐1/MAFbx in chick skeletal muscle. (17th August 2015) - Nakashima, Kazuki; Ishida, Aiko; Ijiri, Daichi; Ohtsuka, Akira
Abstract: Expression of atrogin‐1/MAFbx, a muscle‐specific E3 ubiquitin ligase, is high under catabolic conditions, that result in muscle atrophy. Messenger RNA (mRNA) expression of atrogin‐1/MAFbx is increased by the glucocorticoid dexamethasone in mammalian skeletal muscle. This study investigated the effects of dexamethasone on expression of atrogin‐1/MAFbx in skeletal muscle of neonatal chicks and in chick myotubes. Chicks were given a single intraperitoneal injection of dexamethasone at a concentration of 10 mg/kg body weight. Twenty‐four hours after dexamethasone administration, the Pectoralis muscle weight of chicks was decreased. mRNA expression of atrogin‐1/MAFbx in skeletal muscle of chicks was significantly increased by dexamethasone administration. Expression of other proteolytic‐related genes (20S proteasome C2 subunit, m‐calpain large subunit, and cathepsin B) in skeletal muscle of chicks was not increased by dexamethasone administration. Chick myotubes were incubated with dexamethasone (1, 10 or 100 µmol/L) for 6 h. Expression of atrogin‐1/MAFbx mRNA in chick myotubes was increased in the presence of all concentrations of dexamethasone. However, expression of other proteolytic‐related genes (20S proteasome C2 subunit, m‐calpain large subunit and cathepsin B) in chick myotubes was not affected by dexamethasone treatment. These results indicate that dexamethasone enhances atrogin‐1/MAFbx expression in chick skeletal muscle, resulting in increased muscle atrophy.